Optimalisasi Self Healing bagi Santri Putri Pondok Pesantren Miftahul Mubtadiin Ar-Ridlo, al-Hamami dan Annur Krempyang Tanjunganom Nganjuk - Slamet Arofik; Hafidzul Umami (LP3M STAI Darussalam Krempyang Nganjuk, 2021)
Social Mapping and social analysis conducted by Pokja 5 at the Mitahul Mubtadiin Ar-Ridlo, al-Hamami and Annur Kremp Islamic boarding schools showed that each cottage during the Covid-19 pandemic needed activities that had a